Platform Trust, e-WOM, and Gen Z Purchase Intention: Mediating Role of Retailer Trust - Lady Lady; Hepy Hefri Ariyanto; Cindy Olivia (goodwood publishing, 2026)
Purpose: This study aims to examine the influence of trust in the platform and electroEnic Word-of-Mouth (e-WOM) components social media communication, ratings and reviews, and recommendations and references on purchase intention through the mediating role of trust in the retailer among Gen Z consumers. Research Methodology: This study utilized a quantitative explanatory design with purposive sampling (N=301). Data were collected using a 5-point Likert scale instrument and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) via SmartPLS 4 software. Results: Trust in the platform significantly acts as an antecedent that enables all e-WOM components. Specifically, social media communication and recommendation and reference are primary drivers of trust in the retailer and purchase intention. In contrast, ratings and reviews do not significantly impact trust in the retailer or purchase intention, leading to the rejection of the corresponding mediation hypotheses. Conclusions: Purchase decisions among Gen Z consumers are more effectively driven by institutional trust in the platform and interactive communication signals than by traditional static rating systems. The findings indicate that peer-driven validation and platform security provide more reliable cues for this demographic group than conventional feedback mechanisms. Limitations: The study is limited by its specific urban geographic context and structural model fit, which requires further refinement in future research. Contributions: This study contributes to digital marketing strategy, social commerce platform management, and the literature on consumer behavior.